বঙ্গবন্ধু, জিয়া ও মঞ্জুর হত্যাকাণ্ড : জতুগৃহ একটিই - আনোয়ার, মোঃ নূরুল (ঢাকা : ঐতিহ্য প্রকাশনী, 2015)
Investigative write-ups on the assassination of Sheikh Mujibur Rahman, Ziaur Rahman and Manzur.
In Bengali.
Keywords: Politics and government; Bangladesh -- Politics and government